Improvement of the Engineering Properties of A-3 Soil through the Addition of Clay - Zaynab omer Alqadhqad; Shrifa Mohmed Elhamroni; Heba Ayad Arebi Jebali (African Journal of Advanced Pure and Applied Sciences, 2025)
Sandy soils are characterized by their small particle size, uniform gradation, and lack of cohesion, making them vulnerable to erosion and displacement by natural factors. In Libya, particularly in the western regions, sandy soils are widely distributed. Therefore, it is essential to investigate the properties of this soil type. This paper presents the laboratory results of a study on the effect of adding clay (specifically Gharyan clay) to A-3 sandy soil. The clay was added at varying proportions (0%, 3%, 6%, 9%, 12%) to evaluate its impact on improving the cohesion between soil particles, thereby enhancing soil stability and strength. The laboratory results demonstrated that the geotechnical properties of A-3 soil could be improved through the addition of clay. The compaction characteristics of the soil improved with specific clay percentages, and the dry density increased proportionally with the amount of clay added. Furthermore, direct shear test results indicated a notable improvement in the cohesive strength of the modified soil. This improvement was primarily dependent on the type and percentage of the added clay.